Turmeric oil as antioxidation agent for fresh cut fruits: article / Nur Atiqah Ahmad, PM Dr. Junaidah Jai and Miss Zatul Iranati Md. Sharif - Ahmad, Nur Atiqah; Jai, Junaidah; Md. Sharif, Zatul Iranati (2017)
Nowadays, people are more aware of the healthy eating habit and therefore, due to safety reason, the demand to use natural additives as antioxidation agents for fresh cut products like fresh cut fruits is increasing. This is because the use of synthetic and chemical preservatives has gained a lot of attention to the public since some of it causes odd allergic reactions towards sensitive individuals. Furthermore, the basis appearance of the fresh cut product like fresh cut fruits has to be appealing during the time of purchase because it will be judged by the customer and the appearance of the fresh cut fruits will be the decision-maker for the customer on whether to buy the product or not to buy it. In this research project, edible coating will be used to prevent the enzymatic browning of the fruit (apple) that caused by the Polyphenol Oxidase (PPOs). Starch and glycerol will be used in the formulation of edible coating film and turmeric oil will be added as the additives. Turmeric oil is one of the antioxidation agents that come from spices and herbs. With a ratio of starch:glycerol, 1:0.25, turmeric oil will be added to the formulation and homogenized for 5 minutes at 16000 rpm. Then, the prepared apple slices will be dipped into the emulsion and the coated and uncoated apple slices will be stored and compared afterwards. The coated and uncoated apple slices will be compared by their weight loss, colour changes and sensory evaluation. Also, the degree of oxidation will also be characterized using the assay for PPO activity method.